A new laboratory test to help diagnose a specific type of pemphigoid. (3rd February 2020) - Giurdanella, F.; Nijenhuis, A.M.; Diercks, G.F.H.; Jonkman, M.F.; Pas, H.H.
Summary: An autoimmune disease is a condition where the body sees one of its own proteins as foreign and will try to destroy it. There are various types of autoimmune diseases and one rare form is anti‐laminin‐332 mucous membrane pemphigoid, a severe chronic disease which causes blistering of the mucous membranes in the mouth, eyes, nose and airways, the oesophagus and the genital region. The disease is characterized by IgG (antibodies) which attack a protein called laminin‐332 that is essential for an intact skin. Binding of IgG to laminin‐332 results in inflammation, forming erosions and blisters. There are other forms of mucous membrane pemphigoid that look similar and diagnosis is therefore difficult. A commercial laboratory test that can find the antibodies in the blood is not available. In this study from the Netherlands, the authors developed a simple and specific method to detect the IgG against laminin‐332, called keratinocyte footprint assay. They cultured (meaning grew in a lab) keratinocytes, which are the main cells of skin, on small glass disks. In culture, cells move over the glass and thereby, like slugs, leave behind a trail. These trails contain laminin‐332. After culture the glass disks are air dried and stored in a freezer. When a diagnosis of anti‐laminin‐332 is suspected a disk is taken out and serum (part of the blood) of the patient is brought onto the disk. If IgG to laminin‐332 is present this will bind to the trails. After an hour the disks are rinsed and a fluorescent substance that binds to IgG is put onto the disk. The disks are then investigated under a fluorescent microscope and if the trails are fluorescent, that is proof that the patient has anti‐laminin‐332 antibodies. Comparing blood samples of healthy persons and patients with other autoimmune diseases showed that this method is very specific and sensitive, meaning it is accurate. This summary relates to the study: Keratinocyte footprint assay discriminates antilaminin‐332 pemphigoid from all other forms of pemphigoid diseases Abstract : Linked Article: Giurdanella et al. Br J Dermatol 2020; 182 :373–381